Performance investigation and improvement of linear vernier permanent magnet motor for servo application - Zhou, You (2023)
With its high thrust density and low force ripple, the linear vernier permanent magnet motor (LVPMM) is regarded as a good competitor for linear servo applications. However, typical LVPMMs have shortcomings, such as phase imbalance, a long distributed-winding end, and low power factor. The goal of this work is to present a thorough analysis-based approach for performance enhancement that addresses all three flaws while enhancing the LVPMMs high thrust density advantage. Thanks to the proper slot/pole-pair combination, Halbach array PM, and a special three-modular structure, the proposed LVPMM improves thrust density by 28%, reduces force ripple to 1.2%, increases power factor by over 40%, and nearly eliminates three-phase imbalance when compared with those of a conventional LVPMM. Manufacturing and testing a 2.2 kW/2200 N prototype has confirmed the viability of the theoretical analysis and improvement process.